The Effect of Soybean Hulls Substitution Levels to Corn in The Ration on Energy and Protein Digestibility and on Sheep Performance - Rimbawanto, EA; Iriyanti, N (ANIMAL PRODUCTION, 2000)
An experiment was conducted to investigate the effect of soybean hulls levels substitution in to corn as ration in twenty seven rams. The animal had a mean of live weight of 12.86 ± 1.94 kg. Levels of substitution were 0, 50, and 100% or 0, 25, and 50% ration dry matter basis and rations were iso-nitrogeneous. Analysis of variance were conducted for completely randomized design and polynomial orthogonal test were applied for the statistical analysis. Inclusion of soybean hulls in 50% ration dry matter had no effect on daily gain (99.71 ± 22.97 g), and digestible crude protein (62.43 ± 6.56 %). However, dry matter consumption tended to increase linearly and as soybean hulls level increase in the ration (P<0.01). The digestible energy significantly decrease linearly (P<0.01), whereas intake of the energy had same was 1.27 ± 0.33, 1.44 ± 0.17, and 1.23 ± 0.19 Mcal/day for ration containing 0, 25, 50% of soybean hulls, respectively. It was concluded that the soybean hulls may be substituted for corn. (Animal Production 2(2): 98-103 (2000) Key words : soybean hulls, corn, digestibility, daily gain.